ZnO Nanorods Grown on Heterogenous Ag Seed Layers for Single-Cell Fluorescence Bioassays - Phitchaya Muensri; Alongkot Treetong; Katawut Namdee; Panita Kasamechonchung; Tuksadon Wutikhun; Jitapa Sumranjit; Visittapong Yordsri; Bralee Chayasombat; Mati Horprathum; Supanit Porntheeraphat; Narathon Khemasiri; Sakon Rahong; et al. (ACS Applied Nano Materials, 2021)
Here we demonstrate the controllability of the morphology of hydrothermal ZnO nanorods (ZnO-NRs) grown on heterogenous Ag seed layers. By varying the crystal orientation of silver thin films (Ag), a high density of ZnO-NRs could be obtained. We find that the density of ZnO-NRs strongly relates to the peak intensity ratio between (111) and (200) planes of Ag thin films due to a heteroepitaxy between (0002) ZnO and (111) Ag rather than that of grain boundary nucleation and/or surface nucleation. In addition, the optimized heterostructure of ZnO nanorod/Ag arrays is investigated via a critical concentration for nucleation and used as a fluorescence enhancement substrate (FES). The experimental results have shown that the FES presents an ability to detect a biological sample (PC-3 cell) with a high sensitivity and low detection limit of 1 cell/μL. Our results highlight that understanding an important key to control and design the morphology of heterogeneous hydrothermal ZnO-NR growth is essential to open up the opportunities for fundamental studies and applications in high-performance integrated nanodevices.
Keywords: ZnO doping and properties; Quantum Dots Synthesis And Properties; Advanced biosensing and bioanalysis techniques